2006
DOI: 10.2174/092986706776360932
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Transporter Type-1 and its Inhibitors

Abstract: The ionotropic glutamate receptor NMDA is allosterically modulated by glycine, a coagonist, its presence is an absolute requirement for receptor activation. The transport of glycine in glutamatergic synapse is carried out by glycine transporter-1 (GlyT1), a Na+/Cl(-)-dependent carrier molecule. The primary role of GlyT1 is to maintain glycine concentrations below saturation level at postsynaptic NMDA receptors. Several isoforms of GlyT1 (a-e) have been identified, which are expressed both in glial and neuronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 66 publications
(128 reference statements)
0
29
0
Order By: Relevance
“…8 Unfortunately, none of these compounds are expected to be promising drug candidates because of their safety profiles and pharmacokinetics. 9 More recently, second generation non-amino acid type series of compounds have been developed as potent GlyT1 inhibitors. Some of them showed positive results for clinical use in the treatment of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Unfortunately, none of these compounds are expected to be promising drug candidates because of their safety profiles and pharmacokinetics. 9 More recently, second generation non-amino acid type series of compounds have been developed as potent GlyT1 inhibitors. Some of them showed positive results for clinical use in the treatment of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them showed positive results for clinical use in the treatment of schizophrenia. 6,9 In addition, recent reports suggested that GlyT1 inhibitors could be also applied for various disorders such as depression, anxiety, seizures, and neuropathic pain by modulating NMDA receptor or inhibitory GlyRs. 10,11 However, the existence of a correlation between the progress of such diseases and the change of GlyT1 expression and activity remains to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Great number of compounds with diverse chemical structures has been reported to inhibit GlyT-1 activity [15,16]. A major effort has been made to find selective and potent inhibitors of GlyT-1 with pharmacological profile suitable for clinical drug development.…”
Section: Introductionmentioning
confidence: 99%
“…MEGX shows about 80% potency of the parent drug at voltage-dependent sodium channels, while GX and EG are nearly ineffective. Based on structural similarities to the alternative GlyT1 substrate sarcosine, 22 lidocaine metabolites might also affect GlyT1 function. This hypothesis would explain most of the antinociceptive effects of systemic lidocaine application in neuropathic pain.…”
mentioning
confidence: 99%